Ossifying Fibroma pada mandibula pasien anak - Ratih Trikusumadewi Lubis; Fadhlil Ulum Abdul Rahman; Muhammad Adri Nurrahim; Lusi Epsilawati; Eka Marwansyah Oli'i (Ikatan Radiologi Kedokteran Gigi Indonesia, 2020)
Objectives: To view a case report of mandibular ossifying fibroma (OF) in pediatric male. Case Report: A 12 year old child came to RSHS with a panoramic radiograph with the chief complaint of swelling in the right mandible. Panoramic radiograph shows well-defined mixed lesions with radiolucent content and snowflake-like opaque. MDCT shows a superior-inferior and bucco-lingual extension of the lesion. The suspicion of this case leads to Ossifying Fibroma with differential diagnosis of Adenomatoid Odontogenic Tumor (AOT) and Calcifiying Ephitelial Odontogenic Tumor (CEOT). Conclusion: OF cases in children, especially mandibular, are very rare, where the characteristics of the lesion can be well defined through the help of panoramic radiographs and MDCT. OF is a lesion that has benign characteristics with well-defined borders, and the most important lies in the presence of wrapping capsules and mixed internal structures accompanied by snowflake-like calcification.